Implementasi Teori Responsi Butir (Item Response Theory) Pada Penilaian Hasil Belajar Akhir di Sekolah - Sudaryono -- (Jurnal Pendidikan dan Kebudayaan, 2011)
Educational measurement, including measurement of learning outcomes include a variety of fields, depending on the object of learning what to measure. Therefore, the problem in this paper are: 1) whether the item response theory or theories of modern tests can cover weaknesses that exist in classical test theory, 2) how the item response theory implementations in addressing issues of national exams so that no advantaged groups and disadvantaged groups as a result of measurement that is not fair? The purpose of writing this article is to explain the implementation of item response theory in a cover up weaknesses in classical test theory and address the issues of national examinations, so that no group is disadvantaged or advantaged as a result of measurement that is not fair. Item response theory is an alternative option that aims to break away from dependence on a given test with a sample of test participants. In this case, although the questions are done by a brilliant student or students who are less intelligent, an indication of the level of difficulty of a problem remains unchanged. There are three assumptions that must be met in item response theory, namely: 1) unidimention; 2) local independence, and 3) invariance. While there are three characteristic points, namely: 1) the item difficulty, 2) the different grains, and 3) the level of true coincidence in point. To measure the ability of the test participants are very diverse in the premises, such as the National Examination, should be used is also an examination or test different levels of difficulty because, to be fair and accurate results. Participants test or exam is working on a test or exam because of different levels of difficulty, it can be compared to his ability, provided the questions in the exam are derived or extracted from a question bank that has been calibrated with the concept of item response theory.Â ABSTRAKPengukuran pendidikan meliputi pengukuran hasil belajar dari berbagai bidang, tergantung objek hasil belajar apa yang ingin diukur. Oleh karena itu, yang menjadi permasalahan dalam artikel ini: 1) apakah teori responsi butir atau teori tes modern bisa menutupi kelemahan-kelemahan yang ada pada teori tes klasik; 2) bagaimana implementasi teori responsi butir dalam mengatasi permasalahan-permasalahan ujian nasional sehingga tidak ada kelompok yang diuntungkan dan kelompok yang dirugikan akibat pengukuran yang tidak adil? Tujuan dari penulisan artikel ini adalah menjelaskan implementasi teori responsi butir dalam menutupi kelemahan yang ada pada teori tes klasik dan mengatasi permasalahan ujian nasional, sehingga tidak ada kelompok yang dirugikan maupun diuntungkan akibat pengukuran yang tidak adil. Teori responsi butir merupakan alternatif pilihan yang bertujuan melepaskan diri dari ketergantungan tes yang diberikan dengan sampel peserta tes. Dalam hal ini walaupun soal-soal tersebut dikerjakan oleh siswa yang pandai atau siswa yang kurang pandai, indikasi tingkat kesukaran suatu soal tetap tidak berubah. Ada tiga asumsi yang harus dipenuhi dalam teori response butir, yaitu: 1) unidimensi; 2) independensi lokal; dan 3) invariansi sedangkan karakteristik butir ada tiga, yaitu: 1) taraf sukar butir; 2) daya beda butir; dan 3) tingkat kebetulan betul pada butir. Untuk mengukur kemampuan peserta tes yang sangat beragam di Indonesia, seperti Ujian Nasional, seharusnya digunakan juga ujian atau tes yang berbeda tingkat kesukaran soalnya, supaya adil dan juga akurat hasilnya. Peserta tes atau ujian yang mengerjakan tes atau ujian yang berbeda tingkat kesukaran soalnya, tetap bisa dibandingkan kemampuannya, asalkan soal-soal dalam ujian tersebut berasal atau diambil dari bank soal yang sudah dikalibrasi dengan konsep item response theory.